2021
DOI: 10.3390/ph14050386
|View full text |Cite
|
Sign up to set email alerts
|

A Flavonoid-Rich Extract from Bergamot Juice, Alone or in Association with Curcumin and Resveratrol, Shows Protective Effects in a Murine Model of Cadmium-Induced Testicular Injury

Abstract: It is known that cadmium damages testis structure and functionality. We examined the effects of nutraceuticals such as a flavonoid-rich extract of bergamot juice (BJe), alone or in association with curcumin (Cur) and resveratrol (Re), on mice testicular dysfunction caused by cadmium chloride (CdCl2). Controversial data on the protective effects of Cur and Re are available, while no evidence on the possible role of BJe exists. Adult male C57 BL/6J mice were administered with CdCl2 and treated with Cur, Re, or B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Biologically active compounds, such as nutraceuticals, antioxidants and anti-inflammatory agents, may provide beneficial effects and counteract Cd toxicity through targeting these molecular pathways. Some promising examples among these compounds are polyphenolic substances [ 43 , 72 , 73 ], myo-inositols [ 67 , 74 ], resveratrol [ 75 ] and flavonoids [ 76 , 77 ]. Giovanni et al reported that treatment with myo-inositol protected against Cd-induced damages in mice kidney, significantly lowered TUNEL positive cells number, and increased glutathione content and glutathione peroxidase activity in kidney.…”
Section: Resultsmentioning
confidence: 99%
“…Biologically active compounds, such as nutraceuticals, antioxidants and anti-inflammatory agents, may provide beneficial effects and counteract Cd toxicity through targeting these molecular pathways. Some promising examples among these compounds are polyphenolic substances [ 43 , 72 , 73 ], myo-inositols [ 67 , 74 ], resveratrol [ 75 ] and flavonoids [ 76 , 77 ]. Giovanni et al reported that treatment with myo-inositol protected against Cd-induced damages in mice kidney, significantly lowered TUNEL positive cells number, and increased glutathione content and glutathione peroxidase activity in kidney.…”
Section: Resultsmentioning
confidence: 99%
“…The BJe used in this research was already used in our previous research [ 21 , 33 , 40 ]. Its quali-quantitative analysis showed that neohesperidin (94.00 mg/g), naringin (92.4 mg/g), melitidin (56.2 mg/g), hesperetin (51.9 mg/g), neoeriocitrin (48.6 mg/g) and naringenin (27.3 mg/g) were the most abundant flavonoids.…”
Section: Methodsmentioning
confidence: 99%
“…challenge with CdCl 2 was performed for 14 days. The doses of all substances employed were selected in accordance with previous studies [ 17 , 18 , 21 , 33 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Twenty-four hours after the last treatment, all mice were sacrificed with an overdose of ketamine and xylazine (75/10 mg/kg i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors, in fact, showed that flavonoids restored the depletion of antioxidants as they antagonized the effect of Cd on antioxidant enzyme activity or increased GSH content, improving the antioxidant capacity of the body. In parallel, a flavonoid rich-extract of bergamot juice counteracted both testicular and kidney damage induced by Cd exposure in rats [174,175]. Another research asserts that flavonoids reduced the chromosomal aberration regarding to structure and number of spermatocytes due to their detoxification action that protect protein and DNA from free radicals, and hence from cancer [173].…”
Section: Cadmium (Cd)mentioning
confidence: 98%